Pengaruh Pengetahuan Pajak, Kesadaran Wajib Pajak, dan Program Pemutihan Pajak Pada Kepatuhan Wajib Pajak Kendaraan Bermotor - Darmayani, Sang Ayu Putu Sri; Hasibuan, Henny Triyana (E-Jurnal Akuntansi; Vol 32 No 9 (2022), 2022)
The purpose of the research is to determine the factors that influence taxpayer compliance, namely tax knowledge, taxpayer awareness, and tax whitening programs. The study was held at the SAMSAT Bangli Joint Office. Respondents in the study amounted to 100 participants, selected through purposive sampling method. Data collection was carried out by distributing questionnaires directly and using google forms. Data were analyzed by multiple linear regression analysis. The results showed that tax knowledge, taxpayer awareness, and vehicle tax whitening programs had a positive effect on motor vehicle taxpayer compliance. Keywords: Knowledge; Awareness; Pemutihan Pajak Program; Taxpayer Compliance